2022
DOI: 10.1016/j.ejpn.2021.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Development of muscle tone impairments in high-risk infants: Associations with cerebral palsy and cystic periventricular leukomalacia

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Fine motor skill and assessment can be measured on tests like the Bayley Scales of Infant and Toddler Development®, allowing for comparisons against age‐based normative standards and indicating neurodevelopmental progress 37 . Muscle tone, whether hyper‐ or hypo‐tonic, can also provide information about neurological involvement as well as caloric expenditure 38 . A literature search verified the suggested components, and they were added to Round 2 of the modified Delphi survey for panelist consideration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine motor skill and assessment can be measured on tests like the Bayley Scales of Infant and Toddler Development®, allowing for comparisons against age‐based normative standards and indicating neurodevelopmental progress 37 . Muscle tone, whether hyper‐ or hypo‐tonic, can also provide information about neurological involvement as well as caloric expenditure 38 . A literature search verified the suggested components, and they were added to Round 2 of the modified Delphi survey for panelist consideration.…”
Section: Resultsmentioning
confidence: 99%
“…37 Muscle tone, whether hyper-or hypo-tonic, can also provide information about neurological involvement as well as caloric expenditure. 38 A literature search verified the suggested components, and they were added to Round 2 of the modified Delphi survey for panelist consideration. Both muscle tone and fine motor skills achieved consensus.…”
Section: Domain 2: Body Composition and Metabolismmentioning
confidence: 99%
“…Twenty-three articles were excluded following primary database full-text review: eleven articles did not describe hypotonia measurement [48][49][50][51][52][53][54][55][56][57][58]; five articles described some aspects of hypotonia measurement but had already been fully evaluated in an included review or synthesis [1,5,6,17,19]; five articles described the assessment of passive muscle tone only [59][60][61][62][63]; one article described hypertonia assessment only [64]; and, in addition, a scoping review of muscle tone evaluations [65] included only 2/84 studies evaluating hypotonia. Citation searching revealed that one used an electro-mechanical machine [66] and the other only measured passive limb tone [67]; therefore, the latter review was also excluded.…”
Section: Resultsmentioning
confidence: 99%
“…muscle tone only [59][60][61][62][63]; one article described hypertonia assessment only [64]; and, in addition, a scoping review of muscle tone evaluations [65] included only 2/84 studies evaluating hypotonia. Citation searching revealed that one used an electro-mechanical machine [66] and the other only measured passive limb tone [67]; therefore, the latter review was also excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Motor disorders are the most common symptoms in these patients and are produced by damage in the motor brain cortex and the descending medullar pathways, particularly the corticospinal tract [21,22]. Muscle impairments due to spasticity or hypertonia, stiffness, weakness or hypotonia, reduced strength or muscle pain are some examples of these motor symptoms [23,24], which reduce joint range of motion, selective motor control and gross motor skills [25], impairing the performance of activities of daily living [26,27]. In addition, visual or vestibular disturbances produce gait [28] and balance disorders [29], which increase the risk of falls.…”
Section: Introductionmentioning
confidence: 99%